STATE OF THE TOURISM INDUSTRY OF KYRGYZSTAN FOR 2023 - Kermaliev R. S.; Dyldaev M. M.; Ableshov T. A.; Temirbek uulu I. (Vestnik Issyk-Kulʹskogo universiteta)
In this article, the authors revealed the main extent of the advantages of the tourism industry of Kyrgyzstan, through the prism of statistics. The country’s successes in the development of service and tourism industries and a socially oriented approach to the affairs of the local community require methodical study. With all the existing and accumulated systemic problems in the development of the tourism industry of Kyrgyzstan, there are prospects for their productive solution. The modern development of tourism in the Kyrgyz Republic depends on two factors: the availability of natural and recreational resources and the socio-economic prerequisites for their use. The comparison of these two factors determines the specialization of the tourist and recreational complex and the prospects for its development. When organizing recreation, natural factors and socio-economic objects appear both as conditions and as recreation resources. From the above, we see unconditional prospects for the development of the tourism industry of Kyrgyzstan, where the strengths are the unique natural landscapes of the country. Their rich and pronounced attractiveness is highly valued by tourists from all over the world.